The Influence of Bioproduct Zamin–M On Some Flavonoids of Artichoke Cynara Scolymus L. - Sobirova Mukaddas Batirovna; Murodova Sayyora Sobirovna (Genius Publishing Group, 2021)
In this paper, the experimental data on the effect of the biological product Zamin-M, based on a group of phenolic compounds in artichoke leaves are provided. Experimental results showed that the amount of quercetin flavonoids in 70% alcoholic extract was 0.09 mg/g, which is 1.6 times higher in control variants than control plants treated with NH4NO3 + biological product. The amount of rutin in the control variant was 0.0879 mg/kg, which is 2.2 times less than in plants treated with Zamin-M, 2.3 times more than in plants treated with NH4NO3 and NH4NO3 + Zamin -M ". The amount of cynaroside in 70% of the alcoholic extracts of the leaves of the experimental variant was 8.25 mg/g, which is 1.62 times more than in control plants treated with NH4NO3, 2.3 times more than in plants treated with NH4NO3 + a bioproduct, 2.3 times more than untreated plants. The obtained results indicate that the treatment of plants with the bioproduct Zamin-M with compared to mineral fertilizers NH4NO3 has an effective influence on the metabolic profile, which is associated with the role of secondary metabolites in the plant Cynara scolymus L.
Keywords: Cynara scolymus; Bacillus subtilis SKB 30; bioproduct; flavonoid